2005
DOI: 10.1002/eji.200425941
|View full text |Cite
|
Sign up to set email alerts
|

β1 integrins are not required for the maintenance of lymphocytes within intestinal epithelia

Abstract: b 1 integrins are thought to play a central role in maintaining lymphocytes within mucosal epithelia via their interactions with extracellular matrix proteins and subepithelial cellular components within and underlying the basement membrane. In the current study type a (CD8abTCRab) and type b (CD8aaTCRcd and CD8aaTCRab) intraepithelial lymphocyte (IEL) subsets within the mouse small intestine were found to express functional b 1 integrin and the b 1 integrin a chain partners a 1 , a 2 , and a 4 . Using inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
3
8
1
Order By: Relevance
“…ADAP is required for TCR‐dependent integrin activation of both β1 and β2 integrins, molecules that have been implicated in lymphocyte trafficking and adhesion 7. Both of these families of integrins appear to be dispensable for homing of CD8αα T cells to the intestine 44, 45; however, it is not known whether ADAP regulates expression or function of β7 integrins, proteins thought to be important for selective trafficking of IEL 46, 47. Experiments to determine the expression and function of β7 integrins and their ligands, as well as the functional consequence of CD8αα T cell deficiency, in ADAP‐deficient mice are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…ADAP is required for TCR‐dependent integrin activation of both β1 and β2 integrins, molecules that have been implicated in lymphocyte trafficking and adhesion 7. Both of these families of integrins appear to be dispensable for homing of CD8αα T cells to the intestine 44, 45; however, it is not known whether ADAP regulates expression or function of β7 integrins, proteins thought to be important for selective trafficking of IEL 46, 47. Experiments to determine the expression and function of β7 integrins and their ligands, as well as the functional consequence of CD8αα T cell deficiency, in ADAP‐deficient mice are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…α1β1 integrin, α4β1 integrin, and β2 integrin) (149–151). As in CD103‐deficient mice, no or only a partial reduction in IELs was seen following the disruption of each of these integrins, suggesting that other integrins and/or molecules may compensate for their lack (151, 152). Additionally, we previously reported that IELs expressed the EC adhesion molecule (Ep‐CAM) (153) ().…”
Section: Iel Trafficking Pathwaymentioning
confidence: 90%
“…IELs express multiple β 1 integrins that can interact with components of epithelial basement membranes and mucosal mesenchymal cells [153, 154], but β 1 integrins are not required to retain IELs within intestinal epithelia [154]. Similarly, mice chimeric for β 1 associated α chains, α 4 , α 5 and α V , have normal numbers of IELs [155].…”
Section: αEβ7 Integrin and Its Ligand E-cadherinmentioning
confidence: 99%